2000
DOI: 10.1046/j.1365-201x.2000.00719.x
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous nitric oxide in the control of skeletal muscle oxygen extraction during exercise

Abstract: Our previous studies uncovered an inhibitory effect of nitric oxide (NO) on leg skeletal muscle respiration in dogs at rest. The role of NO in the modulation of O2 consumption and O2 extraction in hindlimb muscle during elevated metabolic states was investigated in chronically instrumented dogs while walking and at three exercise intensities which markedly increased hindlimb blood flow. Walking resulted in increased O2 consumption by 17 +/- 4 mL min-1 and O2 extraction from 24 +/- 1 to 37 +/- 8%, with no alter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
52
4

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(66 citation statements)
references
References 36 publications
10
52
4
Order By: Relevance
“…These findings have been interpreted as an O 2 delivery limitation owing to reduced muscle blood flow. Consistent with this interpretation, there are reports of no effect (1,4) or an increase (35) in muscle V O 2 during "submaximal" exercise in animals where increased O 2 extraction compensates for a lower blood flow. In humans, NOS inhibition alone has no effect on V O 2 across the exercising leg, but when combined with PG synthesis, inhibition by indomethacin, a significant reduction in blood flow is compensated for by varying levels of O 2 extraction (14,15,28,33).…”
Section: R96supporting
confidence: 65%
See 1 more Smart Citation
“…These findings have been interpreted as an O 2 delivery limitation owing to reduced muscle blood flow. Consistent with this interpretation, there are reports of no effect (1,4) or an increase (35) in muscle V O 2 during "submaximal" exercise in animals where increased O 2 extraction compensates for a lower blood flow. In humans, NOS inhibition alone has no effect on V O 2 across the exercising leg, but when combined with PG synthesis, inhibition by indomethacin, a significant reduction in blood flow is compensated for by varying levels of O 2 extraction (14,15,28,33).…”
Section: R96supporting
confidence: 65%
“…In animals, NOS inhibition has been shown to lower muscle V O 2 during evoked contractions (2,20,22,30,31,41), while other studies show no effect (1,4) or an increase (35) in muscle V O 2 during voluntary exercise. In humans, NOS inhibition alone has been found to have little or no effect on V O 2 across the exercising leg or forearm measured by the Fick method (15,28,33).…”
mentioning
confidence: 94%
“…This is in accordance with in vitro studies which suggest that NO competes with oxygen and tonically inhibits mitochondrial respiration by binding to the cytochrome c oxidase complex (3,4,8,9,22). Some animal studies have also previously found increased V O 2 when NO formation is blocked (33)(34)(35). Previous studies that have blocked NOS in humans by infusion of either L-NAME or L-NMMA (10,27) have shown a similar lowering of resting blood flow as in the current study but no effect on oxygen uptake.…”
Section: Discussionsupporting
confidence: 79%
“…By use of in vitro preparations, it has been demonstrated that the primary effect of exogenous NO on mitochondrial activity is a reversible and competitive inhibition of cytochrome oxidase activity (5,6,32). Some animal studies have subsequently found evidence that NO tonically inhibits mitochondrial respiration in vivo (33)(34)(35), but there has not been evidence for this in humans (10,27,31). It is well shown with various methods that prostanoids can act synergistically with NO to regulate vascular function in health and disease (2,19,23,30,31), but COX inhibition may also have direct effects on cellular aerobic respiration by affecting uncoupling (17,20,23).…”
mentioning
confidence: 99%
“…4 -6 We have shown that NO plays an important role in the modulation of oxygen consumption (V O 2 ) and oxygen extraction in hindlimb skeletal muscle at elevated metabolic states during walking or running whether or not blood flow increases. 7 Given that the balance between oxygen utilization and oxygen supply is a major factor responsible for the ability to maintain long-term exercise and support maximal exercise performance, 8 a loss of NO production might lead to decreased exercise capacity by increasing V O 2 . More recently, we have shown that there is a limitation of exercise capacity in male mice with defects in the expression of endothelial NO synthase (eNOS), which is associated with a greater increase in whole-body V O 2 than in wild-type mice.…”
mentioning
confidence: 99%